Container Quay Crane Structural Response under Trolley Traveling - Xiong Hu; Kai Dong; Pei Zheng; Zhiwei Sun; Sen Mu (Advances in Materials Science and Engineering)
Structural response of quay crane should take more attention with the growth of worldwide logistics demand and quay crane size. This paper analyzes the response mechanism of the metallic structure of the quay crane induced by trolley traveling. An on-site test has been conducted. The time domain of crane girder acceleration signal shows that the main influence of the trolley traveling on crane structure is the high-frequency impact passing through the hinge point. The spectrum shows the main frequency of structure vertical vibration and impact vibration. Single girder model and theoretical derivation reveal that the vertical displacement response is quasistatic. A refined numerical model of the whole crane structure is established. The interaction between the trolley and the girder is realized by S-M contact method. The calculated results are basically consistent with the measured signal. The acceleration result indicates the same information as on-site test such that the structural acceleration response of in-service crane is affected by trolley in high-frequency band. The displacement results in three directions of 10 points on the girder show that the trolley traveling has significant effect on the vertical displacement. The lateral displacement shows the eccentric loading condition of girder. The displacement spectrum indicates that the trolley has little dynamic effect on displacement response of crane structure. The response can be treated as quasistatic.